Alveolar bone changes around upper incisors in Class I non extraction patient after orthodontic treatment using cone beam computed tomography (Orthodontic Journal of Nepal, 2021)
Introduction: The position and movement of incisors play important role in orthodontics. Efficient tooth movement and stable position cannot be ensured without adequate alveolar bone support. The bone loss estimated by traditional radiograph is always less than real bone loss so CBCT is currently best to evaluate bone changes. The purpose of this study was to use CBCT to evaluate and compare changes in alveolar bone thickness and Vertical alveolar bone height around maxillary anterior teeth of Class I malocclusion patient after orthodontic treatment.Materials and Method: Forty patients with Class I occlusion between ages of 12 to 18 years were selected. The cone beam computed tomography (CBCT) and lateral cephalograms were taken before treatment (T0) and after treatment (T1). The lateral cephalograms were used to assess the change in tooth inclination whereas CBCT was used to assess the alveolar bone change. All the data were statistically analyzed using paired sample t-test and independent sample test.Result: Significant changes in alveolar bone thickness and vertical bone height were found on the palatal surface of the anterior teeth compared to that of labial surface with significant change in tooth inclination.Conclusion: Based on the results, we can conclude that the palatal alveolar bone loss and vertical bone loss was greater than that of the labial alveolar bone.